Implementing a modified World Health Organization safe childbirth checklist in health centers of Ethiopia: a pre and post intervention study - Hailemariam Segni Abawollo; Zergu Tafesse Tsegaye; Binyam Fekadu Desta; Tsega Teferi Mamo; Haregewoin Getachew Mamo; Zebyderu Tesfay Mehari; Zenawork Kassa Gebremedhin; Ismael Ali Beshir (BMC, 2021)
Abstract Background Childbirth is a complex process, and checklists are useful tools to remember steps of such complex processes. The World Health Organization safe childbirth checklist is a tool used to improve the quality of care provided to women giving birth. The checklist was modified by Ministry of Health and was introduced to health centers in Ethiopia by the USAID Transform: Primary Health Care Activity. Methods A pre and post intervention study design with prospective data collection was employed. The availability of essential childbirth supplies and adherence of health care providers to essential birth practices were compared for the pre and post intervention periods. Results The pre and post intervention assessments were conducted in 247 and 187 health centers respectively. A statistically significant improvement from 63.6% pre intervention to 83.5% post intervention was observed in the availability of essential childbirth supplies, t (389.7) = − 7.1, p = 0.000. Improvements in adherence of health care providers to essential birth practices were observed with the highest being at pause point three (26.2%, t (306.3) = − 10.6, p = 0.000) followed by pause point four (21.1%, t (282.5) = − 8.0, p = 0.000), and pause point two (18.2%, t (310.8) = − 9.7, p = 0.000). The least and statistically non-significant improvement was observed at pause point one (3.3%, t (432.0) = − 1.5, p = 0.131). Conclusion Improvement in availability of essential childbirth supplies and adherence of health care providers towards essential birth practices was observed after introduction of a modified World Health Organization safe childbirth checklist. Scale up of the use of the checklist is recommended.